Adherence: Its Role in Achieving Control Over Bronchial Asthma in Children - G. A. Novik; E. A. Vishneva; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2015)
This article is concerned with the problem of obtaining control over bronchial asthma in children. The goal of treating any allergic disease is to gain control over the symptoms and a maximum decrease in future risks (both aggravations and negative therapy side effects). The authors present an algorithm of determining the level of control over bronchial asthma. A complex approach towards treatment is shown. It has been noted that, despite a significant movement towards the understanding different aspects of child asthma and the current efforts in creating guides concerning its treatment, a great number of patients are still incapable of controlling the illness. One of the main reasons is the lack of adherence demonstrated by the patients and their parents towards medical recommendations. This article deals with the main reasons why the patients do not follow the recommendations of doctors. The authors no only discuss the ways of increasing the patient-doctor collaboration, but also offer modern and innovative solutions which should help to increase the adherence to the designated therapy and thus the control over child asthma.